The deformation induced tunable topology in controlling of band gap characteristics for stepped phononic crystals. (1st August 2022) - Wang, Y.F.; Guo, J.C.; Zhang, Z.
Abstract: A new deformation mode induced by welding in the fabrication is proposed for the controlling of the band gap characteristics in stepped phononic crystals (PnCs). The systematic investigations show that the stiffness change is the key physical nature connecting the deformation induced tunable topology with the wave attenuations in PnCs. The formed fillet weld can lead to 39.02%–53.10% variations of the second band gap from the theoretical designed values. Further increase of the weld distortion can lead to the increase of the band gap width and the decrease of center frequency. By optimally controlling of the weld distortion and the formed fillet weld, weld induced distortion can cause the generation of a wide new band gap with a width of 3742.4 Hz at the center frequency of 3297.7 Hz. Compared with the initial design, the new band gap width is increased by 139.7% and the center frequency is reduced by 31.9%. Highlights: Tunable topology state was designed by the TIG welding deformation mode. New band gap was formed by weld deformation mode. Wide band gap with low center frequency can be well controlled.